High-Fidelity Tidal Current Modelling in Irish Sites to Inform the Feasibility of Novel Energy Use Cases (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal current modelling is crucial for evaluating the feasibility and further optimising the placement of tidal energy converters (TECs), as TECs rely on foundational data on flow strength provided by such modelling investigations. Moreover, flow simulation informs subsequent resource modelling, enabling a more accurate energy potential assessment. The embedded technology and structural design of a TEC are specifically tailored to meet the requirements of distinct flow conditions. While ongoing efforts primarily focus on modelling TECs to evaluate structural performance and anchorage under varying flow scenarios, their operational performance remains less explored, as most devices are still in the prototype and testing phase in real tidal environments. This underscores the need for a deeper understanding of local hydrodynamics, as the consistency and reliability of steady flows at prospective TEC sites is vital for optimising operational performance. Furthermore, identifying suitable flow areas for energy capture and conducting in-depth hydrodynamic modelling to pinpoint sustained high-flow zones remain limited. These perspectives form the foundation of our current modelling research.Many studies highlight the importance of high-resolution modelling for understanding local hydrodynamic conditions, which are vital for renewable energy applications. Reports show that existing tidal current modelling for Irish sites is often limited by resolution, undermining model confidence. To address this limitation, our model aims to develop a higher-resolution approach for the selected sites of interest. Prior to modelling, a literature review was conducted to compile tidal resource databases and identify high tidal energy sites in Ireland. The methodologies used in the development of existing models were explored to assess their reliability across adopted resolutions, which informed our decision on the resolution for the current model. The site selection process for modelling involved analysing locations within selected Irish sites that exhibit potential for novel tidal energy use cases, such as powering aquaculture, lighthouses, or other activities traditionally not powered by ocean energy. Our preliminary review found that the Shannon Estuary in the southwest holds significant potential due to its strong tidal currents and the presence of various economic activities, including aquaculture and lighthouse operations. Site identification was followed by modelling.A two-dimensional model was developed using the EFDC modelling tool to simulate surface current speeds of ambient and wind-driven tidal flows. The model was constructed with simple forcing parameters, assuming barotropic conditions, while ensuring careful attention to model resolution. This resolution was determined based on insights from the relevant review, balancing the desired level of detail with available computational resources. The model was validated using measured and modelled data at the site obtained from existing sources.The model produces several outputs crucial for the development of ocean energy, including: (1) site-specific understanding for effective TEC deployment and operation, (2) identification of locations with maximum energy yield, (3) guidance for energy potential modelling, (4) flow maps supporting optimal TEC placement, (5) flow patterns aiding TEC operations, (6) insights into powering novel use cases. This research improves simulation accuracy and flow predictions, ultimately providing valuable information for the commercial expansion of tidal energy projects in Ireland.